Catalogue of flat-band stoichiometric materials - Regnault, Nicolas; Xu, Yuanfeng; Li, Ming-Rui; Ma, Da-Shuai; Jovanovic, Milena; Yazdani, Ali; Parkin, Stuart S. P.; Felser, Claudia; Schoop, Leslie M.; Ong, N. Phuan; Cava, Robert J.; Elcoro, Luis; et al. (Nature (London), 2022)
Topological electronic flattened bands near or at the Fermi level are a promising route towards unconventional superconductivity and correlated insulating states. However, the related experiments are mostly limited to engineered materials, such as moiré systems 1 – 3 . Here we present a catalogue of the naturally occuring three-dimensional stoichiometric materials with flat bands around the Fermi level. We consider 55,206 materials from the Inorganic Crystal Structure Database catalogued using the Topological Quantum Chemistry website 4 , 5 , which provides their structural parameters, space group, band structure, density of states and topological characterization. We combine several direct signatures and properties of band flatness with a high-throughput analysis of all crystal structures. In particular, we identify materials hosting line-graph or bipartite sublattices—in either two or three dimensions—that probably lead to flat bands. From this trove of information, we create the Materials Flatband Database website, a powerful search engine for future theoretical and experimental studies. We use the database to extract a curated list of 2,379 high-quality flat-band materials, from which we identify 345 promising candidates that potentially host flat bands with charge centres that are not strongly localized on the atomic sites. We showcase five representative materials and provide a theoretical explanation for the origin of their flat bands close to the Fermi energy using the S -matrix method introduced in a parallel work 6 . A catalogue of the naturally occurring three-dimensional stoichiometric materials with flat bands around the Fermi level provides a powerful search engine for future theoretical and experimental studies.